Development of a correlation to estimate the fatigue strength for steels based on low-cost tests - Martínez, Alexander; Jaimes, Alban; Uribe, Iván; Serna, Aníbal (CT&F - Ciencia, Tecnología y Futuro, 2020)
Fatigue cracking in metallic materials occurs mainly due to the effect of cyclic stresses and their variation of magnitude over time. To evaluate the fatigue strength based on S-N curves, many tests are needed, which require a lot of time and incur high costs. For this research, several tests were conducted on examples of high-strength steel to determine their mechanical properties, chemical composition and fatigue. It was found that (Charpy V Notch) CVN impact toughness, the percentage of alloying elements and the mechanical properties of the tension test show a positive lineal effect in relation to the fatigue strength of the materials evaluated. Finally, a correlation was found that showed a very good fit between the experimental fatigue data and the predicted values. The correlation, based on Charpy impact energy tests, the relation to the yield stress, the ultimate stress, and the hardness of the material, allows one to predict resistance to fatigue at a low cost.